Experimental investigation and two-phase flow simulation of oil and nanofluids on micro CT images of sandstone for wettability alteration of the system - Ali, H. (Elsevier B.V., 2021)
This work provides an analysis of the effect of nanofluids on the wettability of sandstone for the application of enhanced oil recovery. The wettability of sandstone with brine and nanofluids of ZnO, BiFeO3, and SrFeO3 is studied experimentally using contact angle calculations. Also, the direct simulations for the displacement of oil with brine and nanofluids are carried out on a micro-CT scanned porous sandstone structure for the measurement of capillary pressure and relative permeability. Fluid properties such as viscosity and density of the nanofluids, brine, and oil to be used in simulations were obtained using viscometer and densimeter. The experimental results show that the contact angle of crude oil on the sandstone surface has a higher value for nanofluids as 125.89° for ZnO, 122.88° for BiFeO3, and 104.98 for SrFeO3 as compared to brine 28.66°, which means the wettability of the system changes from oil-wet to water-wet by the addition of nanofluids. The simulation results indicate that BiFeO3 nanofluid has a greater tendency to change the wettability of porous medium as compared to brine, ZnO, and SrFeO3 nanofluids, as it shows better values of relative permeability and capillary pressure. © 2021 Elsevier B.V.